Effects of compression clothing in elite female ice speed skaters - Born, D.-P.; Herlitz, B.; Zinner, C.; Richter, K.; Lefter, M.; Sperlich, B. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Compression clothing has become increasingly popular in particular in endurance sports due to the evidence of improved performance in running and cycling (Bernhardt et al. 2005, Chatard et al. 2004). While compression is a possible mean to increase venous return (Ibegbuna et al. 2003) there are conflicting results regarding the use of compression on blood lactate concentration and oxygen uptake (Ali et al. 2010, Berry et al. 1987, Bringard et al. 2006, Rimaud et al. 2010). Since elite speed skaters produce a high muscle force during the long gliding phases with restricted intramuscular blood flow (Foster et al. 1999) elite speed skaters could benefit of compression due to 1) improved blood flow, 2) increased muscle oxygenation, 3) less blood lactate accumulation and 4) increased performance. Therefore, the aim of the study was to evaluate the effect of lower body compression clothing on performance and cardiorespiratory as well as metabolic parameters in female elite ice speed skaters. Methods: 6 female elite German ice speed skaters volunteered for this study (60.5±7.3kg, 168±6cm, 19.8±3.3%, VO2max 57.8±5.9 ml/min/kg). All participants performed two on-ice 3000m trails with and without lower-body compression clothing in a random order and an incremental test to determine VO2max. During the trails VE, VO2, VCO2 and HR were measured continuously with a portable spirograph (Cortex Metamax & Polar). Tissue saturation index (TSI) and blood volume (tHb) were determined by the concentrations of oxy-, deoxy- and total haemoglobin measured with near-infrared spectroscopy (NIRS, Portamon). Capillary blood samples were collected before, immediately after, 10 and 30 minutes after the exercise and analysed using amperometric-enzymatic determination of lactate (Eppendorf). Additionally, the subjects rated their perceived exertion (BORG´s scale) before and after both trails. Results: The application of lower-body compression clothing did not show any benefits on performance determined by the time to complete 3000m. Furthermore, no differences were observed in respiratory measurements (VE, VO2, RER), HR, La, NIRS data (TSI, tHb) or RPE (p > 0.05). Discussion & Conclusion: The results show no detectable effects of compression on performance or any physiological measurements in female elite ice speed skaters. These results go in line with earlier studies showing no benefits of compression in well-trained endurance athletes (Ali et al. 2010, Sperlich et al. 2011).